1995
DOI: 10.3109/00016349509009945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term administration of an oral contraceptive containing ethinylestradiol and cyproterone acetate on lipid metabolism in women with polycystic ovary syndrome

Abstract: Lipid and lipoprotein changes observed after treatment could be due to the estrogen dominance of the treatment. The plasma concentration of triglycerides and total cholesterol during treatment does not change appreciably and the LDL-C/HDL-C ratio improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 11 publications
2
26
0
3
Order By: Relevance
“…In a prospective open-label study evaluating lipid profiles and glucose homeostasis in 72 women with PCOS treated with ethinyl estradiol/cyproterone acetate for 3 years, the investigators observed an increase in triglycerides and high-density lipoprotein (HDL) cholesterol and a decrease in the low-density lipoprotein (LDL)/HDL ratio in women PCOS after the treatment. More importantly, insulin and glucose plasma concentrations did not change (69).…”
Section: Long-term Use Of Ocps and Cardiometabolic Risk In Pcosmentioning
confidence: 82%
“…In a prospective open-label study evaluating lipid profiles and glucose homeostasis in 72 women with PCOS treated with ethinyl estradiol/cyproterone acetate for 3 years, the investigators observed an increase in triglycerides and high-density lipoprotein (HDL) cholesterol and a decrease in the low-density lipoprotein (LDL)/HDL ratio in women PCOS after the treatment. More importantly, insulin and glucose plasma concentrations did not change (69).…”
Section: Long-term Use Of Ocps and Cardiometabolic Risk In Pcosmentioning
confidence: 82%
“…Oral intake of oestrogen is well known to increase plasma triglyceride levels. 24,25 A known major adverse effect of flutamide treatment is dose-dependent hepatotoxicity. 5,6 In our study, we administered low-dose flutamide, and hepatic enzymes were found to be within normal ranges indicating no liver toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…20 Previous studies have found that combined oral contraceptives are effective for the reduction of androgen levels and hirsutism in women with PCOS; these studies have mainly focused on drospirenone, desogestrel and cyproterone acetate. 8,9,19 These studies were small in size and not powered to assess thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Two studies assessed the metabolic effects of combined oral contraceptives in PCOS, but these studies had small sample sizes and could not evaluate for cardiovascular events. 9,10 Although women with PCOS have an increase in both cardiovascular risk factors and subclinical cardiovascular disease, 11 recent guidelines have concluded there are no data in the literature assessing the association between the use of oral contraceptives and cardiovascular disease among women with PCOS. 2 Because combined oral contraceptives are the mainstay…”
mentioning
confidence: 99%